Early applied electric field stimulation attenuates secondary apoptotic responses and exerts neuroprotective effects in acute spinal cord injury of rats. (16th April 2015) - Zhang, C.; Zhang, G.; Rong, W.; Wang, A.; Wu, C.; Huo, X.
Graphical abstract: Highlights: Electric field stimulation (EFS) with the cathode distal to the lesion was conducted in rats of spinal cord injury. The injury potentials were attenuated by EFS. Neuroprotective effects were demonstrated by functional and historical evaluations. The underlying mechanisms may include the inhibition of apoptotic responses. Abstract: Injury potential, which refers to a direct current voltage between intact and injured nerve ends, is mainly caused by injury-induced Ca 2+ influx. Our previous studies revealed that injury potential increased with the onset and severity of spinal cord injury (SCI), and an application of applied electric field stimulation (EFS) with the cathode distal to the lesion could delay and attenuate injury potential formation. As Ca 2+ influx is also considered as a major trigger for secondary injury after SCI, we hypothesize that EFS would protect an injured spinal cord from secondary injury and consequently improve functional and pathological outcomes. In this study, rats were divided into three groups: (1) sham group, laminectomy only; (2) control group, subjected to SCI only; and (3) EFS group, received EFS immediately post-injury with the injury potential modulated to 0 ± 0.5 mV by EFS. Functional recovery of the hind limbs was assessed using the Basso, Beattie, and Bresnahan (BBB) locomotor scale. Results revealed that EFS-treated rats exhibited significantly better locomotor function recovery. Luxol fast blue staining was performed to assess the spared myelin area. Immunofluorescence was used to observe the number of myelinated nerve fibers. Ultrastructural analysis was performed to evaluate the size of myelinated nerve fibers. Findings showed that the EFS group rats exhibited significantly less myelin loss and had larger and more myelinated nerve fibers than the control group rats in dorsal corticospinal tract (dCST) 8 weeks after SCI. Furthermore, we found that EFS inhibited the activation of calpain and caspase-3, as well as the expression of Bax, as detected by Western blot analysis. Moreover, EFS decreased cellular apoptosis, as measured by TUNEL, within 4 weeks post-injury. Results suggest that early EFS could significantly reduce spinal cord degeneration and improve functional and historical recovery. Furthermore, these neuroprotective effects may be related to the inhibition of secondary apoptotic responses after SCI. These findings support further investigation of the future clinical application of EFS after SCI.